Detection of obstetric anal sphincter injuries using machine learning-assisted impedance spectroscopy: a prospective, comparative, multicentre clinical study - Borycka, Katarzyna; Młyńczak, Marcel; Rosoł, Maciej; Korzeniewski, Kacper; Iwanowski, Piotr; Heřman, Hynek; Janku, Petr; Uchman-Musielak, Małgorzata; Dosedla, Erik; Diaz, Enrique Gonzalez; Sudoł-Szopińska, Iwona; Mik, Michał; et al. (Scientific reports, 2025)
To evaluate the clinical performance and safety of the ONIRY system for obstetric anal sphincter injuries (OASI) detection versus three-dimensional endoanal ultrasound (EAUS). A prospective, comparative, multicentre, international study. Poland, Czechia, Slovakia, and Spain. 152 women between the first moments up to 8 weeks after vaginal delivery. Participants underwent EAUS and were allocated to groups based on OASIS classification: A (no perineal tear), B (1st or 2nd degree tear), or C (3rd or 4th degree, anal sphincters affected). Electric impedance was measured in the anal canal using the ONIRY system. The primary endpoint was the diagnostic outcome of impedance spectroscopy versus EAUS. Adverse events were collected. Part II involved in silico modelling and 10-time 10-fold cross-validation for automated analysis. Accuracy, sensitivity, and specificity. 30 women were allocated to group A, 61 to group B, and 61 to group C. The diagnostic outcome was determined for 147 participants. The accuracy, sensitivity, and specificity of the ML-assisted impedance spectroscopy were 87.0 ± 0.5%, 90.6 ± 2.0%, and 84.6 ± 1.9%, respectively, compared with EAUS. After data cleaning, the performance metrics of the proposed final ML model for ONIRY were: 90.0 ± 0.4%, 90.0 ± 1.2%, and 90.0 ± 0.7%, respectively. No adverse device effects or deficiencies were observed. By enabling early identification of sphincter injuries, ML-assisted impedance spectroscopy facilitates timely diagnosis and intervention, potentially reducing long-term complications such as faecal incontinence. Its rapid, bedside application in obstetric settings supports immediate postpartum care, complementing digital rectal examination and optimizing clinical decision-making.
Keywords: Anal sphincter; Faecal incontinence; Sensitivity and Specificity; senzitivita a specificita; Perineal tear; Pregnancy; Humans; Obstetric anal sphincter injury (OASI); Female; impedanční spektroskopie; dospělí; Machine Learning; Dielectric Spectroscopy; lidé; anální kanál; Adult; Rapid diagnostics; ženské pohlaví; strojové učení; vedení porodu; Delivery, Obstetric; těhotenství; Machine learning; Anal Canal; Impedance spectroscopy; Clinical study; prospektivní studie; Prospective Studies